The impact of social media in crisis communication management of corporate brands - Victorino, Mariana Hidalgo Barata Martins (2016)
This research focuses on the impact of social media in crisis communication management, in light of the new environment in which organizations have to manage threats to their corporate brands’ reputation. Driven by a twenty-year experience in corporate communication, as well as by our knowledge of the existing theories and research in this field, we set out to question the extent to which the speed and reach that social media impose on communication are having an impact in the management of crisis communication. Adopting an interpretivist approach, this thesis will be addressing the field of crisis communication management from the perspective of the corporate brand with specific emphasis on the consequences that a crisis situation may have on its reputation. The main objective of this research is therefore to understand how the changes brought about by the onset and dominance of social media are influencing organizations in their definition of specific methodologies to manage crisis communication; and whether social media is having a catalytic effect on the management of issues that may damage the corporate brands’ reputation. Grounded on the theoretical framework provided by the study of existing literature in the fields of corporate brand, corporate brand reputation, corporate brand communication, crisis communication, and social media, our research will combine different empirical methods of a qualitative nature in order to attain a broader understanding of the profound changes brought by social media to crisis communication management. For this purpose, we started by conducting a set of interviews with qualified specialists from Academia in the fields of corporate communication, reputation, and crisis communication, which assisted us in defining the scope of the research field and the relevance of the object to be investigated, as well as to validate our conclusions. However, the core of our empirical work is based on eighteen in-depth interviews with corporate communication managers of large corporations operating in Portugal. To complement the output of the interviews, we explored two specific crisis situations for their unique significance: the first crisis communication case to have arisen on Facebook in Portugal, affecting a corporate brand’s reputation; and an internal perspective on the crisis situation triggered by social media that led to the cancelation of the Facebook page of the most important energy company in Portugal. We complemented this analysis with inputs from secondary sources about the impact of social media in crisis communication management. An interpretivist analysis of the results allowed to conclude that there are significant changes in top management’s mindset and approach to crisis communication towards a more open and transparent attitude in face of these situations. However, although organizations claim to have structured methodologies in place to manage crisis communication and to have incorporated social media into their communication strategy, most of them have not yet implemented updated crisis communication management procedures. Based on the unanimous views from both experts and communication managers we confirmed that social media is having a catalytic role on organizations’ approach to crisis communication management of the corporate brand. The fact that most organizations feel uncomfortable with the lack of control and the uncertainty that social media entails, coupled with a broader range of threats brought by this media, is not only increasing their awareness of the need to manage their reputation effectively, but also also reshaping top management’s outlook on this field. This research process led us to the definition of the determining variables for corporate brands’ crisis communication management in the era of social media, as well as to the complementing of the existing SMCC (Social Mediated Crisis Communication) model developed by Jin, Liu and Austin in 2011. This model was is intended to help crisis managers understand how the public produces, consumes, and shares crisis information via social media. The field of crisis communication involves complex issues that organizations would rather keep silent or very restricted in view of the potential negative impact they may have on their reputation. It is therefore a challenging field of research for whose progression we aspire to contribute.